Dihydro-5,6-dehydrokavain (DDK) from Alpinia zerumbet: Its Isolation, Synthesis, and Characterization - Tran Dang Xuan; Rolf Teschke (Molecules, 2015)
Dihydro-5,6-dehydrokavain (DDK) is the major and most promising component of the tropical plant Alpinia zerumbet (shell ginger), a species of the ginger family Zingiberaceae. Alpinia zerumbet is known for its human use as a traditional herbal medicine, food, and dietary supplement. With its α-lactone ring, DDK belongs to the large chemical group of kavalactones, which are also found in kava (Piper methysticum), another herbal medicine; DDK is characterized by a double-bond linkage at positions 5,6 and the absence of a double-bond linkage at positions 7,8. This dissociates DDK from other kavalactones with their linkages at positions 7,8 and 5,6 that are both either completely saturated or unsaturated, or may have an unsaturated bond at the position 7,8 as well as a saturated bond at the position 5,6. DDK is easily identified and quantified by HPLC and GC. DDK contents in fresh leaves, stems and rhizomes range from 80 to 410 mg/g, requiring solvent extraction procedures to ensure high DDK yield. This is best achieved by hexane extraction from fresh rhizomes that were previously boiled in water, allowing DDK yields of up to 424 mg/g. Successful synthesis of DDK can be achieved by asymmetric pathways, whereas its simple chemical structure facilitates the synthesis of DDK derivatives by HCl hydrolysis. Thus, all synthesized products may be used for various commercial purposes, including the potential development of promising antiobesity pharmaceutical drugs, preparation of specific and safe dietary supplements, and use as effective natural herbicides or fungicides.